Nanodiamond-mediated delivery of microRNA-7 for the neuroprotection of dopaminergic neurons - Han, Yuping; Yao, Yue; Wen, Xinyi; Wang, Hao; Li, Shurong; Su, Bingyin (Frontiers in Bioengineering and Biotechnology, 2025)
Parkinson’s disease (PD) is a neurodegenerative disorder characterized by the gradual loss of dopaminergic neurons in the substantia nigra and the accumulation of α-synuclein aggregates known as Lewy bodies. MicroRNA-7 (miR-7) targets the gene SNCA, which encodes α-synuclein, reducing its expression and alleviating neuronal damage in PD. Regulating the post-transcriptional levels of α-synuclein through miR-7 effectively inhibits its production. Herein, we use nanodiamonds as carriers to deliver miR-7 (N-7), which can effectively protect dopaminergic neurons. Dopaminergic neurons efficiently take up N-7 and express miR-7. N-7 inhibits the expression of α-synuclein, reduces oxidative stress and restores dopamine levels effectively. These findings suggest that nanocomposites have significant potential in treating PD.